(untitled) (Research, Society and Development, 2021)
Objective: to analyze nursing practices in studies within the psychiatric/mental health area. Methods: An integrative review process was used to guide this study. Four databases— LILACS, MEDLINE, SCOPUS and CINAHL —were searched for eligible studies using relevant keywords. PICo strategy was employed for selection of studies. Primary studies published in Portuguese and English language from 2010 to 2020 were reviewed following a pre-determined inclusion criteria. Studies that met the inclusion criteria were appraised using the recommendation from Stetler at al. (1998).Results: 15 publications were analyzed. The evidence showed the diversity of nursing practices involved medication administration, measurement of vital signs, hygiene, nutrition, in addition to actions aimed at self-esteem and self-care. Studies about nursing actions focused on the uniqueness of the patient were also identified. From the analyzed articles, it was possible to extract a total of 15 practical nursing activities, which, in fact, demonstrates a wide range in the understood role of the nursing profession. Assistance to patients’ medication was the most cited activity by the authors. Conclusions: the implementation of nursing practices in mental health must be seen as a challenge that goes beyond the medication standard and creates care proposals with a focus on the patient. This patient centered care was present in the work dynamics of the CAPS.